2019
DOI: 10.18203/2320-1770.ijrcog20196020
|View full text |Cite
|
Sign up to set email alerts
|

A study on correlation between laterality of placenta on mid trimester ultrasonography and perinatal outcome

Abstract: Background: Fetus is dependent on placenta for supply of nutrients from mother. Objective of this study was to assess the relationship between laterality of placenta by mid-trimester ultrasonography and perinatal outcome.Methods: It was a prospective observational study conducted between June 2016 to June 2017 at Burdwan Medical College, West Bengal. Participants were uncomplicated pregnant women having 18-24 weeks gestation attending antenatal clinics and admitted in ward who underwent obstetric sonography in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 9 publications
1
3
1
Order By: Relevance
“…25 The implications of placental implantation site have been established in previous studies and include mainly pregnancy complications such as pre-eclampsia, postpartum hemorrhage, low APGAR score, and fetal growth restriction. 2,[12][13][14][15]17 The higher rate of preterm births in the lateral placenta group in present study support our initial assumption and is in agreement with the literature. 2,3,12,13,18 For example, in the much larger study by Granfors et al, 2 a significant association was found between lateral placentation (1860 women) and preterm birth.…”
Section: Characteristicssupporting
confidence: 92%
See 4 more Smart Citations
“…25 The implications of placental implantation site have been established in previous studies and include mainly pregnancy complications such as pre-eclampsia, postpartum hemorrhage, low APGAR score, and fetal growth restriction. 2,[12][13][14][15]17 The higher rate of preterm births in the lateral placenta group in present study support our initial assumption and is in agreement with the literature. 2,3,12,13,18 For example, in the much larger study by Granfors et al, 2 a significant association was found between lateral placentation (1860 women) and preterm birth.…”
Section: Characteristicssupporting
confidence: 92%
“…Regarding our primary outcome measure, there was a clear tendency toward lower newborn birth weight in the women with a laterally located placenta, albeit without clear statistical significance according to standard parameters ( P = 0.07). A review of the literature yielded different references to the effect of lateral implantation, either positive or negative, on newborn birth weight 2,12,13,15,16 . The lack of statistical significance in our study might be attributed to the relatively small size of the lateral placenta group.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations